2007
DOI: 10.1681/asn.2007040444
|View full text |Cite
|
Sign up to set email alerts
|

COL4A3/COL4A4 Mutations Producing Focal Segmental Glomerulosclerosis and Renal Failure in Thin Basement Membrane Nephropathy

Abstract: Mutations in the COL4A3/COL4A4 genes of type IV collagen have been found in ϳ40% of cases of thin basement membrane nephropathy, which is characterized by microscopic hematuria and is classically thought to cause proteinuria and chronic renal failure rarely. Here we report our observations of 116 subjects from 13 Cypriot families clinically affected with thin basement membrane nephropathy. These families first came to our attention because they segregated microscopic hematuria, mild proteinuria, and variable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
178
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(199 citation statements)
references
References 49 publications
12
178
2
4
Order By: Relevance
“…Light microscopy revealed FSGS in three of these 16 patients. Previous studies of large Greek Cypriot pedigrees led to the suggestion of a causal relationship between heterozygous COL4A3/COL4A4 mutations and FSGS (20,21 (4) showed normal expression in glomeruli in all patients in this study. We previously also showed normal expression of a5(4) in GBM in 29% of patients with XLAS and 20% of patients with ARAS (16,18).…”
Section: Discussionsupporting
confidence: 58%
“…Light microscopy revealed FSGS in three of these 16 patients. Previous studies of large Greek Cypriot pedigrees led to the suggestion of a causal relationship between heterozygous COL4A3/COL4A4 mutations and FSGS (20,21 (4) showed normal expression in glomeruli in all patients in this study. We previously also showed normal expression of a5(4) in GBM in 29% of patients with XLAS and 20% of patients with ARAS (16,18).…”
Section: Discussionsupporting
confidence: 58%
“…In view of the above findings and the findings by Voskarides et al [4], it was tempting to hypothesize that TBMN is not always a benign condition but rather a situation which predisposes COL4A3/COL4A4 heterozygous carriers to a higher risk for proteinuria or FSGS and renal failure, when another genetic modifier is co-inherited. In a recent publication in this journal Tonna et al [12] reported on 56 TBMN patients (on the basis of persistent hematuria), some of whom also had proteinuria of ≥300 mg/l, or ≥500 mg/l.…”
mentioning
confidence: 94%
“…The term TBMN, with only few exceptions, has largely been used as a synonym for benign familial microscopic hematuria, which nearly always is the only symptom, with excellent prognosis [1][2][3]. Those few exceptions are worth concentrating on, in view of a recent publication from my laboratory, which provides voluminous exceptional data from a population on the island of Cyprus [4]. In that report we described 13 families with the dual diagnosis of TBMN and focal segmental glomerulosclerosis (FSGS), while, in ten of them, we identified three heterozygous mutations in the COL4A3/COL4A4 genes.…”
mentioning
confidence: 99%
“…TBMN associated with heterozygous COL4A3/COL4A4 mutations was reported to show a causal relationship with the development of focal segmental glomerulosclerosis (FSGS) and renal failure [4,9,10]. TBMN itself may be a primary factor leading to chronic renal insufficiency and FSGS may be a consequence of proteinuria, though our patients had no sign of FSGS under light and electron microscopy at the time of biopsy.…”
Section: Case Reportmentioning
confidence: 55%